The Development Of Chemistry Virtual Laboratory On Colloidal System To Improve Generic Science Skills - Khaeruman, Khaeruman; Darmatasyah, Darmatasyah; Hulyadi, Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This study animed to obtain the from and feasibility of teaching materials interactive multimedia based on virtual laboratory on colloidal system concept for SMA. The development model used in this study was 4D namely Define, Design,, Development, And Disseminate. But in this study only came to Development stage. The velopment result was validated by 2 lecturers, 1 teacher and 10 students in Ma Nurul Muhsinin. Based on the assessment of two lecturers as validatorn got the average (71,3%) with the appropriate category, the validation result from the subject teachers got percentage of (77,7%) with appropriate category, and the limited trial result by 10 students got percentage of (80,8%) with decent category. So it can be concluded that the feasibility of interactive multimedia based on virtual laboratory on colloidal system material for SMA/MA/SMK was feasible to use.